20-Hydroxyecdysone increases levels of transient gene expression in transfected Drosophila cells. - Sinclair, J H (1987)
Methods for increasing the transient level of expression of transfected DNA in cultured Drosophila cells have been examined. Here we show that cells exposed to the steroid hormone 20-hydroxyecdysone for 48h prior to transfection show an 4 to 5 fold increase in the levels of expression of transfected DNA. By analysis, in situ, this increase appears to be due to an increase in the number of cells expressing the transfected DNA. The stimulation in levels of expression is not correlated to any specific DNA sequence, nor does it occur if cells are exposed to hormone post-transfection.